2021
DOI: 10.1186/s12885-021-09097-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety and antibody response to two-dose SARS-CoV-2 messenger RNA vaccination in patients with multiple myeloma

Abstract: Background Patients with multiple myeloma (MM) were excluded from the original SARS-CoV-2 mRNA vaccine trials, which may influence vaccine hesitancy in this population. We prospectively characterized the safety and immunogenicity of two-dose SARS-CoV-2 mRNA vaccination in 44 patients with MM, who underwent vaccination from 12/17/2020 to 3/18/2021. Results Rates adverse reactions were low and consistent with those documented in vaccine trials. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
(9 reference statements)
0
11
1
Order By: Relevance
“…Initial vaccination (2x Comirnaty) of the patient described by us while still receiving Pomalidomide treatment as maintenance therapy after remission of multiple myeloma failed to induce SARS-CoV-2 seroconversion ( Figure 1 and Figure 2 ). This was in contrast to other reports showing that ongoing Pomalidomide treatment did not affect the response [ 17 , 18 , 19 ]. Common risk factors for vaccination failure such as low B cell counts (<30/µL), current anti-CD38 monoclonal antibody treatment or active disease with more than one treatment line were also absent in our patient [ 17 , 20 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Initial vaccination (2x Comirnaty) of the patient described by us while still receiving Pomalidomide treatment as maintenance therapy after remission of multiple myeloma failed to induce SARS-CoV-2 seroconversion ( Figure 1 and Figure 2 ). This was in contrast to other reports showing that ongoing Pomalidomide treatment did not affect the response [ 17 , 18 , 19 ]. Common risk factors for vaccination failure such as low B cell counts (<30/µL), current anti-CD38 monoclonal antibody treatment or active disease with more than one treatment line were also absent in our patient [ 17 , 20 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In this setting, there have been reports showing the response to vaccines in subjects with hematological cancer [23][24][25][26][27][28], such as Case 1 in this study. For example, Benda et al observed a total of 259 hemato-oncological patients vaccinated with two 30 µg doses of BNT162b2 administered 21 days apart.…”
Section: Discussionmentioning
confidence: 74%
“…Vaccinated myeloma patients were at >350% less risk of severe outcomes and 331% less risk of death following COVID-19 infection compared to unvaccinated myeloma patients. An earlier study demonstrated that 2/3 rd of vaccinated myeloma patients show some response to mRNA vaccines, although vaccination may only provide partial protection from infection, while 1/3 rd failed to respond based on background IgG levels of 50IU/ml 15 . However, the threshold/cut-offs were primarily probabilistic, with no clinical follow-up correlating relevant anti-spike IgG levels with protection in vaccinated patients.…”
Section: Discussionmentioning
confidence: 99%